If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(-5x+2)+4x=8x
We move all terms to the left:
9(-5x+2)+4x-(8x)=0
We add all the numbers together, and all the variables
-4x+9(-5x+2)=0
We multiply parentheses
-4x-45x+18=0
We add all the numbers together, and all the variables
-49x+18=0
We move all terms containing x to the left, all other terms to the right
-49x=-18
x=-18/-49
x=18/49
| 3x+4x=5x+60 | | x–8=-11 | | 5x+12=6x-44 | | a=2*15 | | -9x=-10x+6 | | 3x-2(-7+13)=-196 | | -251=7(7n-5)+5n | | X^2-x-184=0 | | 5(3x-7)=-140 | | 3x+2(-6x+10)=-88 | | -3x–8=-11 | | -14=3(v+7)-8v | | 17x-14=3x+4 | | x-(.75)=20 | | p(30309)=28000(1.02)^30309 | | 8.2k+1.5=3.2k-0.9 | | 3*(1/3x-12)=7x+6 | | -4(-4x+2)=-13x-3 | | 16/g;g=4 | | 3(-x=1)+2=2(2x-4)-1 | | 7(m-6);m=8 | | 16x+7=4x-3 | | 3x+4x=x+60 | | 242=11(x-4) | | 10v-7v=15 | | -3(2y-4)=12-6y | | 2(3x+2)=2(2x-1) | | Y-3y+3y-y=0 | | 7m-6;m=8 | | 2.3+x/3=-2.5 | | 3x+(x/2)=42 | | (3*9)*8=98*3)*n |